The management of police specialized tactical units - Mijares, Tomas C. (Charles C Thomas, Publisher, Ltd, 2021)
"A major responsibility of the leadership of any specialized police unit is the awareness of endlessly changing societal, legal, and managerial developments that affect operations. This third edition of The Management of Police Specialized Tactical Units represents a significant updating and expansion of each of the chapters from previous editions. In addition to explaining the steps for developing and maintaining a realistic and effective response to increasingly violent levels of crime, this edition discusses the social, political, and technological matters that must be continuously identified, defined, and resolved prior to the implementation of any substantive or procedural change in tactical policy and practice. Legal and operational guidelines are provided to help tactical leaders to develop their leadership abilities and tactical success, thereby enhancing the tactical unit's ability to safeguard the public. The authors make extensive use of the latest court decisions to provide the legal bases for operations as well as recent case histories to illustrate the various aspects of organizational management. These case histories do much more than summarize the sequence of events. They also point out what was learned from the successes and failures alike. Of particular interest is the new material on how the range of activities assigned to tactical units has expanded dramatically since September 11, 2001 and how the law enforcement community has been forced to respond to its newest critics. Emphasis is placed on how decision-makers must not only be organizational managers and administrators but also on how they should possess a firm grasp of confrontation tactics and leadership principles"--